2017
DOI: 10.1111/dar.12464
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐cultural comparisons of drinking motives in 10 countries: Data from the DRINC project

Abstract: There was broad cross-cultural consistency in the factor structure and mean patterns of drinking motives. Undergraduate students appear to drink mainly for positive reinforcement (i.e. for social and enhancement reasons), although this tendency is particularly pronounced among those from more individualistic countries. [Mackinnon SP, Couture M-E, Cooper ML, Kuntsche E, O'Connor RM, Stewart SH, and the DRINC Team. Cross-cultural comparisons of drinking motives in 10 countries: Data from the DRINC project.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
48
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 26 publications
8
48
1
1
Order By: Relevance
“…As part of a larger program of research examining correlates of drinking motives, participants from this pretest sample who indicated they drink primarily to enhance positive experiences (i.e., enhancement motives; Mean enhancement = 3.21, SD = 0.85) or to cope with negative affect (i.e., coping motives; Mean coping = 1.83, SD = 0.79) were oversampled for participation to ensure the representation of the full range of these motivations, given the high skewness typically observed in these variables. Both distributions of social motives (Mean social = 3.47, SD = 0.92) and conformity motives (Mean conformity = 1.51, SD = 0.63) in the current study are in line with what typically found in previous studies (see Cooper et al., ; Mackinnon et al., ). Descriptive statistics indicated a normal distribution of ASQ subscale scores in this sample.…”
Section: Methodssupporting
confidence: 93%
“…As part of a larger program of research examining correlates of drinking motives, participants from this pretest sample who indicated they drink primarily to enhance positive experiences (i.e., enhancement motives; Mean enhancement = 3.21, SD = 0.85) or to cope with negative affect (i.e., coping motives; Mean coping = 1.83, SD = 0.79) were oversampled for participation to ensure the representation of the full range of these motivations, given the high skewness typically observed in these variables. Both distributions of social motives (Mean social = 3.47, SD = 0.92) and conformity motives (Mean conformity = 1.51, SD = 0.63) in the current study are in line with what typically found in previous studies (see Cooper et al., ; Mackinnon et al., ). Descriptive statistics indicated a normal distribution of ASQ subscale scores in this sample.…”
Section: Methodssupporting
confidence: 93%
“…In spite of the considerable difference in mean levels of drinking motives, alcohol use and adverse consequences found across countries as also reported in other studies , the pattern of association between drinking motives and adverse consequences varied slightly in effect size but was nonetheless generally comparable across all 10 countries under consideration. This finding is in line with hypothesis iv and implies that health promotion efforts that are based on or incorporate drinking motives are likely to be applicable across Europe.…”
Section: Discussionmentioning
confidence: 41%
“…For example, in the U.K. there has been shift towards the acceptance of public drunkenness as evidenced by increasing 'cultures of intoxication' and 'determined drunkenness' (Measham, 2006;Measham & Brain, 2005). Individuals such as students, who may share A C C E P T E D M A N U S C R I P T demographic characteristics, may drink for broadly similar reasons across different countries (Mackinnon et al, 2017). Thus there are likely to be differences within and between countries in those factors which might lead individuals to reduce drinking (Labhart et al, 2017).…”
Section: Accepted Manuscriptmentioning
confidence: 99%